E240V Substitution Increases Catalytic Efficiency toward Ceftazidime in a New Natural TEM-Type Extended-Spectrum β-Lactamase, TEM-149, from Enterobacter aerogenes and Serratia marcescens Clinical Isolates - Perilli, Mariagrazia (American Society for Microbiology (ASM), 2008)
The aim of this study was to characterize a novel extended-spectrum β-lactamase that belongs to the TEM family, the TEM-149 enzyme, and that was isolated from the urine of two hospitalized patients from different hospitals in southern Italy. The peculiarity of this enzyme was the finding of a valine residue at position 240. The array of amino acid substitutions found in TEM-149 was as follows: E104K, R164S, M182T, and E240V. A reversion of a threonine residue at position 182 was also performed to create a new mutant, TEM-149(T182M), in order to assess the contribution of this substitution on the kinetic profile and the stability of TEM-149. The bla(TEM-149) and bla(TEM-149/T182M) genes were cloned into pBC-SK, and the corresponding enzymes were purified from recombinant Escherichia coli HB101 by the same procedure. Both enzymes hydrolyzed all β-lactams tested, with a preference for ceftazidime, which was found to be the best substrate. By comparison of the kinetic parameters of the TEM-149 and the TEM-149(T182M) enzymes, a reduction of the catalytic efficiency for the TEM-149(T182M) mutant was observed against all substrates tested except benzylpenicillin, cefotaxime, and aztreonam. Tazobactam, clavulanic acid, and sulbactam were good inhibitors of the TEM-149 β-lactamase.